(untitled) (New York, 1992)
The book gives an up-to-date background for the planning and design of systems to manage water resources. Economic, social, political, and environmental consideration are important part of the decision-making process. Planning is a complex process in which competing uses for water must be considered in the light of physical, economic, and environmental constraints
Keywords: Hydraulic engineering,Water resources development